Strategi Branding PT Pupuk Kujang dalam Pembentukan Citra melalui Akun Instagram @pupukkujang - Habibah, Dian; Kusumaningrum, Rasti; Teguh Santoso, Made Panji (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Currently, many companies are competing to build their image through social media platforms like Instagram. PT Pupuk Kujang is also using Instagram for branding and engaging with the public to maintain the company's existence. This research aims to uncover PT Pupuk Kujang's branding strategy using the concept of The Circular Model of Some by Regina Luttrell. The research method employed is qualitative with a descriptive approach. It utilizes interview, observation, and documentation techniques. The research findings indicate that in the "Share" stage, PT Pupuk Kujang shares the latest content using a call-to-action method, shares social activity content to build public trust in the company, and provides company contact information on Instagram. In the "Optimize" stage, they monitor trending topics and conduct satisfaction surveys to ensure that @pupukkujang is optimal in sharing content. In the "Manage" stage, the management of @pupukkujang is done manually without using tools. In the "Engage" stage, they target native digital audiences by creating persuasive content without relying on specific brand influencers.Top of Form